Primary Neuronal Precursors in Adult Crayfish Brain: Replenishment from a Non-neuronal Source - Sandeman David C (BMC Neuroscience, 2011)
Abstract Background Adult neurogenesis, the production and integration of new neurons into circuits in the brains of adult animals, is a common feature of a variety of organisms, ranging from insects and crustaceans to birds and mammals. In the mammalian brain the 1st-generation neuronal precursors, the astrocytic stem cells, reside in neurogenic niches and are reported to undergo self-renewing divisions, thereby providing a source of new neurons throughout an animal's life. In contrast, our work shows that the 1st-generation neuronal precursors in the crayfish (Procambarus clarkii) brain, which also have glial properties and lie in a neurogenic niche resembling that of vertebrates, undergo geometrically symmetrical divisions and both daughters appear to migrate away from the niche. However, in spite of this continuous efflux of cells, the number of neuronal precursors in the crayfish niche continues to expand as the animals grow and age. Based on these observations we have hypothesized that (1) the neuronal stem cells in the crayfish brain are not self-renewing, and (2) a source external to the neurogenic niche must provide cells that replenish the stem cell pool. Results In the present study, we tested the first hypothesis using sequential double nucleoside labeling to track the fate of 1st- and 2nd-generation neuronal precursors, as well as testing the size of the labeled stem cell pool following increasing incubation times in 5-bromo-2'-deoxyuridine (BrdU). Our results indicate that the 1st-generation precursor cells in the crayfish brain, which are functionally analogous to neural stem cells in vertebrates, are not a self-renewing population. In addition, these studies establish the cycle time of these cells. In vitro studies examining the second hypothesis show that Cell Tracker™ Green-labeled cells extracted from the hemolymph, but not other tissues, are attracted to and incorporated into the neurogenic niche, a phenomenon that appears to involve serotonergic mechanisms. Conclusions These results challenge our current understanding of self-renewal capacity as a defining characteristic of all adult neuronal stem cells. In addition, we suggest that in crayfish, the hematopoietic system may be a source of cells that replenish the niche stem cell pool.